The effect of smoking on bleeding on probing after nonsurgical periodontal therapy: a quasi-experimental study - Rodrigo ARDAIS; Ticiane de Góes MÁRIO; Jociana BOLIGON; Karla Zanini KANTORSKI; Carlos Heitor Cunha MOREIRA (Sociedade Brasileira de Pesquisa Odontológica, 2014)
The objective of this study was to evaluate the effect of smoking on response to nonsurgical periodontal therapy using the primary outcome measure of bleeding on probing (BoP). An periodontist performed periodontal therapy on 11 smokers and 14 never smokers with periodontitis. Two examiners assessed visible plaque index, gingival bleeding index, probing pocket depth (PPD), BoP, suppuration on probing and clinical attachment level (CAL), at baseline and three months after therapy. BoP was categorized as 0 (absent), 1 (small bleeding point) and 2 (blood flow from the sulcus). Total BoP value was obtained by summing values of 1 and 2. All subjects had significant reductions in mean PPD and percentages of sites with BoP, with no difference between the groups. Only never smokers presented statistically significant CAL gain. BoP was significantly and consistently reduced at sites with initial PPDs of 1-3 mm and 4-6 mm in both groups. At sites with deep PPD ( ≥ 7mm), never smokers showed a greater mean reduction in the number of sites with BoP than did smokers (p < 0.05). Never smokers had significantly greater reduction in BoP 2 than smokers, at sites with moderate and deep baseline PPDs. The first group had a significant increase of BoP 1, at sites with initial PPDs of 4-6 mm. Thus, periodontal therapy reduced BoP in both groups. However, smoking could negatively affect the BoP reduction at deeper sites after nonsurgical periodontal therapy.